Work Readiness of Senior High School Students in the Technical-Vocational-Livelihood Track - Yoshida, Yoshimitsu M. (International Journal of Pedagogy and Learning Community (IJPLC), 2025)
Given the increasing need for skilled labor and persistent concerns regarding the employability of Technical-Vocational-Livelihood (TVL) students, this study examined the work readiness of Senior High School (SHS) TVL students in a School Division in Region 02, Philippines, and investigated how factors such as gender, academic strand, possession of NC II certification, and work immersion duration influence their preparedness for the workforce. Employing a descriptive-causal comparative design with a one-shot survey method, data were collected from 330 TVL students and 108 teachers using a validated 60-item questionnaire that assessed work attitude, technical skills, social skills, and organizational awareness. Student self-assessments were compared with teacher evaluations to identify discrepancies in perceived work readiness. Results revealed that both groups rated overall work readiness as low, with students’ self-ratings consistently exceeding teacher evaluations; significant differences were observed across all dimensions. While gender and academic strand did not yield significant differences, students possessing an NC II certification reported significantly higher work readiness across all dimensions. Furthermore, although variations in work immersion duration did not significantly affect overall readiness, notable differences emerged in technical skills and organizational awareness. These findings offer vital insights for educational stakeholders and policymakers, emphasizing the need for targeted interventions to enhance TVL students’ readiness for the workforce and ultimately improve their long-term employability.